(untitled) (Ciudades, 2025)
The relationship between the physical dimension of housing and the distribution of income in the city is essential to understand urban fragmentation and the territorialization of residential vulnerability. Through the methodological development of a new Housing Indicator for the 2021 Catalogue of Vulnerable Neighborhoods, this article addresses the interrelation between building category obtained from the Cadastre and median income per consumption unit at census section level, focusing on the four largest Spanish cities: Madrid, Barcelona, Valencia, and Seville.